Embracing Vulnerability - Anbeek, Christa (Radboud University Press, 2024)
“I have long argued that we should not avoid life’s all-encompassing fragility but rather embrace it. Fragility, uncertainty, unpredictability, dependence, and porousness, however difficult they often can be, are sources of deep insights. Disruptive experiences bring us into borderlands. They make our vulnerability manifest but also reveal new perspectives and creativity.”